Broken Systems Under Repair: Weaving Ethics of Care and Human Flourishing Into the Work and Lives of Essential Workers - Ellen Scully-Russ EdD (Adult Education Research Conference, 2024)
This empirical paper will report on an innovative participatory action research project, based on Freire cultural circles to raise awareness and provoke moral deliberation about the precarity of essential work and its detrimental impacts on the lives of essential workers.
Keywords: essential worker; moral deliberation; informal and incidental learning